Income contingency and the electorate's support for tuition - Philipp Lergetporer; Ludger Woessmann (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2022)
We show that the electorate's preferences for using tuition to finance higher education strongly depend on the design of the payment scheme. In representative surveys of the German electorate (N>18,000), experimentally replacing regular upfront by deferred income-contingent payments increases public support for tuition by 18 percentage points. The treatment turns a plurality opposed to tuition into a strong majority of 62 percent in favor. Additional experiments reveal that the treatment effect similarly shows when framed as loan repayments, when answers carry political consequences, and in a survey of adolescents. Reduced fairness concerns and improved student situations act as strong mediators.
Keywords: H52; I22; D72; 330; tuition; higher education finance; income-contingent loans; voting